Lived Experiences of Healthcare Workers Infected with COVID-19 in Teaching Hospitals - Mitra Amini; Ali Asghar Hayat; Mohamad Hasan Keshavarzi; Aliakbar Faghihi; Hamid Reza Koohestani (Shiraz University of Medical Sciences, 2023)
Background: With the onset of the coronavirus crisis, the medical treatment staffs were at the forefront of dealing with the disease. The lived experiences in the face of this disease can help better manage the epidemic and identify organizational and individual barriers and challenges. This study aimed to investigate the experiences of medical staff working in COVID- 19 wards in Shiraz teaching hospitals.Methods: The present study is a qualitative study conducted in 2021-2022. A semi-structured interview was used to collect data. Eighteen nurses, physicians, and health workers of Shiraz University of Medical Sciences were employed for the interview. The snowball sampling technique based on the target group was used. Data were analyzed by The Colaizzi seven-step analysis method.Results: Three themes, including "tensions", "material and spiritual support", and "pleasant feeling" and eight sub-themes were extracted. The sub themes were "resilience", "insufficient knowledge", "depression", "expressing gratitude by friends", "public attention", "organizational support", "feeling proud", and "altruism".Conclusion: The present study shows that COVID- 19 caused a lot of pressure on the medical staff during the pandemic, which led to psychological and emotional damage. On the other hand, material and spiritual support played an important role in reducing distress in times of crisis.